0440 Subjective Sleep Outcomes with Lemborexant Among Subjects with Insomnia and Clinically Meaningful Decreases on the Insomnia Severity Index. (25th May 2022) - Roth, Thomas; Moline, Margaret; Pinner, Kate; Yardley, Jane; Pappadopulos, Elizabeth; Malhotra, Manoj
Abstract: Introduction: Lemborexant (LEM) is a dual orexin receptor antagonist approved in multiple countries for the treatment of adults with insomnia. In Study 303 (NCT02952820), LEM provided significant benefit on sleep outcomes including patient-reported (subjective) sleep onset latency (sSOL) and wake after sleep onset (sWASO) versus placebo (PBO). This post-hoc analysis assessed these measures in Insomnia Severity Index (ISI) responders, defined as subjects with clinically meaningful reductions (≥7 points) in ISI total scores (ISI-TS). Methods: Study 303 was a 12-month, PBO-controlled (first 6mo), randomized, double-blind, phase 3 study in subjects with ISI-TS ≥15 (moderate to severe insomnia). Subjects (n=949; Full Analysis Set [FAS]) received LEM (5mg [LEM5]; 10mg [LEM10]) or PBO for 6mo. Changes from baseline (CFB) in sSOL (min) and sWASO (min) at 6mo were analyzed in ISI responders from the FAS and in subjects with severe insomnia (baseline ISI-TS ≥22), using mixed-effect model repeated measurement analysis. Results: At 6mo, 175 (LEM5), 151 (LEM10), and 124 (PBO) subjects were ISI responders; of these, 46 (LEM5), 48 (LEM10) and 29 (PBO) had severe insomnia. CFB in the FAS in median sSOL was significantly greater with LEM5 (−21.8) and LEM10 (−28.2) versus PBO (−11.4; both P<0.001). ISI responders also had significantly greater decreases in sSOL with LEM (LEM5: −26.7, P<0.01; LEM10: −32.6, P<0.001) than PBO (−18.0). In ISI responders from the severe insomnia subgroup, greater CFB in median sSOL was observed with LEM10 (−41.4) than with PBO (−32.1; P>0.05), but not with LEM5 (−32.9, P>0.05).Least-squares mean (standard error) CFB in sWASO in the FAS was −46.8(3.7) with LEM5 (P<0.001), −42.0(3.7) with LEM10 (P<0.05), versus −29.3(3.6) with PBO. In ISI responders, CFB in sWASO was greater with LEM10 (−52.7[4.0], P>0.05) and significantly greater with LEM5 (−58.9[3.8], P<0.01) versus PBO (−43.6[4.4]). In ISI responders from the severe insomnia subgroup, greater CFB was observed with LEM5 (−91.6[9.5]) versus PBO (−70.2[11.1]); P>0.05); CFB with LEM10 (−71.4[9.0]) was similar to PBO. Conclusion: ISI responders including those from the severe insomnia subgroup reported greater CFB in sSOL and sWASO than the FAS that was somewhat dose dependent. LEM generally showed benefit versus PBO. Support (If Any): Eisai Inc.